2015
DOI: 10.12693/aphyspola.127.1136
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization and Thermal Properties of Aluminium Titanate/Talc Ceramic Matrix Composites

Abstract: Talc (3MgO·4SiO2·H2O) has excellent mechanical properties, shock and abrasion resistance, good electrical and thermal shock resistance, softness, isolation, chemical activity, heat resistance and oil absorption properties. Aluminium titanate (Al2TiO5) exhibit extremely good thermal shock resistance and low thermal conductivity coupled with good chemical resistance in molten metals. In the present work, Aluminium titanate/talc ceramics composites with dierent percentages of Al2TiO5 was prepared using powder met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, it was obviously detected that grain growth accompanied by increasing temperature and microcracks located in grain boundary (Figure 4). As is well‐known, the microcracked morphology observed in all SEM images is the inherent feature of AT‐based materials, which is resulted from high anisotropy of axis induced internal stress 7,42–44 . It was noteworthy that interlocked grains contributing to microcracks network structure were prominent in SEM micrographs with a dense body.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Meanwhile, it was obviously detected that grain growth accompanied by increasing temperature and microcracks located in grain boundary (Figure 4). As is well‐known, the microcracked morphology observed in all SEM images is the inherent feature of AT‐based materials, which is resulted from high anisotropy of axis induced internal stress 7,42–44 . It was noteworthy that interlocked grains contributing to microcracks network structure were prominent in SEM micrographs with a dense body.…”
Section: Resultsmentioning
confidence: 60%
“…As is well-known, the microcracked morphology observed in all SEM images is the inherent feature of AT-based materials, which is resulted from high anisotropy of axis induced internal stress. 7,[42][43][44] It was noteworthy that interlocked grains contributing to microcracks network structure were prominent in SEM micrographs with a dense body. Furthermore, the elongated grains were also observed at 1450 • C for both of the samples (as indicated by the dashed outline in Figure 6A,B).…”
Section: Microstructure Analysis Of Fired Ceramicsmentioning
confidence: 99%
“…28,29 Studies have shown that second phase (mullite, feldspar, talc, etc.) [30][31][32][33][34][35] are added to the aluminum titanate ceramic, it can reduce microcrack. Or distributed at the microcrack in the aluminum titanate matrix, the second phase can reduce the degree of lattice distortion of aluminum titanate crystals by physical extrusion, inhibit the further growth and decomposition of aluminum titanate grains, and then improve its thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The monoclinic phase exists at the room temperature and the temperatures greater than 1170 °C it transforms to the tetragonal form. The tetragonal phase is constant at temperatures of 1170 -2370 o C, and the cubic phase occurs at over 2370 °C [1][2][3][4][5][6][7]. The transition from tetragonal form to monoclinic phase (about 9%) undergoes large volume change in microstructure which makes difficult to obtain stable sintered zirconia ceramic products.…”
Section: Introductionmentioning
confidence: 99%